2018
DOI: 10.1186/s12875-017-0705-2
|View full text |Cite
|
Sign up to set email alerts
|

Identifying enablers and barriers to individually tailored prescribing: a survey of healthcare professionals in the UK

Abstract: BackgroundMany people now take multiple medications on a long-term basis to manage health conditions. Optimising the benefit of such polypharmacy requires tailoring of medicines use to the needs and circumstances of individuals. However, professionals report barriers to achieving this in practice. In this study, we examined health professionals’ perceptions of enablers and barriers to delivering individually tailored prescribing.MethodsNormalisation Process Theory (NPT) informed an on-line survey of health pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(58 citation statements)
references
References 20 publications
0
58
0
Order By: Relevance
“…The mixedmethods studies used varying combinations of semistructured interviews, focus groups, survey data, patient data, and narrative and systematic reviews of the literature [31,40,42,43]. The document analysis article adopted a mapping approach and the quantitative paper utilised a cross-sectional survey [54,59].…”
Section: Study Design and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mixedmethods studies used varying combinations of semistructured interviews, focus groups, survey data, patient data, and narrative and systematic reviews of the literature [31,40,42,43]. The document analysis article adopted a mapping approach and the quantitative paper utilised a cross-sectional survey [54,59].…”
Section: Study Design and Methodsmentioning
confidence: 99%
“…The majority (n = 23) of studies reported using NPT in the pilot evaluation of interventions only [32, 36-41, 43-53, 55-58, 61], while five chose NPT as a framework for developing interventions [31,36,54,59,60], and three used the theory in RCTs [33,37,42].…”
Section: Operationalising Normalisation Process Theory In Uk Primary mentioning
confidence: 99%
See 1 more Smart Citation
“…5 Whole-person individually tailored clinical decision making is the expertise of the medical generalist. 6 Medical generalism is a distinct form of clinical practice that is complementary to, but different from, specialist practice.…”
mentioning
confidence: 99%
“…Providing individually tailored care to patients with polypharmacy was the subject of a recent survey led by Dr Reeve. 24 A total of 444 health professionals responded, with nurses making up the majority of respondents (53%); 22% of respondents were GPs and 20% pharmacists. One-third of the respondents claimed to be providing individualised prescribing, with GPs being least likely to be doing so.…”
Section: Individualised Prescribingmentioning
confidence: 99%